2018
DOI: 10.19136/era.a5n13.1393
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein requirement in common snook (Centropomus undecimalis ) juveniles reared in marine and brackish water

Abstract: A total of 300 Centropomus undecimalis juveniles, with an average initial weight of 3.16 0.28 g and average total length of 7.17 0.22 cm, were reared for eight weeks using a recirculating system to determine the dietary protein requirement for their growth and survival. The eect of ve experimental diets containing 40, 45, 50, 55 and 60% total protein content and two salinities (brackish water, BW at 5 UPS and marine water, MW at 36 UPS) were assessed. Fish were fed ve times per day at 2.5% of total biomass. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Besides, higher DPs of 500 and 550 g/kg markedly decreased the PER than it in 450 g/kg level. The decreased trend of PER at higher DP was similar to the result reported by Bartolo et al (). It was reported that an excess of proteins could stimulate increased trypsin production, which increased both satiety and energy costs used for ammonia excretion (Bartolo et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, higher DPs of 500 and 550 g/kg markedly decreased the PER than it in 450 g/kg level. The decreased trend of PER at higher DP was similar to the result reported by Bartolo et al (). It was reported that an excess of proteins could stimulate increased trypsin production, which increased both satiety and energy costs used for ammonia excretion (Bartolo et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…lanceolatus (Rahimnejad et al, ); 480 g/kg and 120–150 g/kg for juvenile northern snakehead fish, Channa argus (Sagada et al, ); 550 g/kg and 70 g/kg for golden mandarin fish, Siniperca scherzeri (Sankian et al, ); 450 g/kg and 50 g/kg for Pseudobagrus ussuriensis fingerlings (Wang et al, ); and 400 g/kg and 80 g/kg for juvenile goldfish, Carassius auratu (Belsare et al, ). The observed differences of required DP and DL could be due to factors such as different species and size, protein and lipid sources, amino acids composition, water temperature, environmental condition, rearing system, non‐protein energy sources and level (Bartolo et al, ; Henry & Fountoulaki, ; Ng et al, ; Rahimnejad et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that a dietary protein level of 400 g kg −1 with 120 g kg −1 lipid could meet the needs for optimal growth of the common snook. However, Concha‐Frías et al (2018) previously observed relatively lower growth (based on SGR) in common snook (3.15 g initial weight) fed 400 g kg −1 protein with 151 g kg −1 lipid and 300 g kg −1 wheat and corn meal, compared to 500 g kg −1 protein with 154 g kg −1 lipid and 140 g kg −1 wheat and corn meal. The differences between studies could have been attributed to those in dietary formulation, particularly digestible carbohydrate inclusion as a dietary non‐protein energy source, which were supplied in a minimal percentage in the test diets of this study (20 g kg −1 corn starch).…”
Section: Discussionmentioning
confidence: 93%
“…Liver enzyme assays were monitored spectrophotometrically by observing changes in the absorbance of NADH/NAD and NADP/NADPH per min at 340 nm for 10 min (Borrebaek et al, 1993; Tranulis et al, 1996). All enzyme activities were measured at 37°C (Bonamusa et al, 1992; Concha‐Frías et al, 2018; Gjellesvik et al, 1992). Digestive and metabolic enzyme activities were reported as mg of soluble protein (specific activity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation